Microstructural evolution and joint strength of Sn-58Bi/Cu joints through minor Zn alloying substrate during isothermal aging - Wang, Fengjiang; Zhou, Lili; Wang, Xiaojing; He, Peng (Journal of alloys and compounds, 2016)
To improve the interfacial microstructure and mechanical behaviors of Sn-58Bi/Cu joint, minor Zn element was alloyed into Cu substrate. The interfacial intermetallic compound (IMC) growth and bending properties of Sn-58Bi/Cu and Sn-58Bi/Cu-2.29Zn were studied with the effect of isothermal liquid and solid aging. Although there was no significant change on the composition, thickness and morphology of interfacial IMC under liquid aging, the depressing of IMC growth at the interface between Sn-58Bi solder and substrate and the avoidance on formation of Cu3Sn IMC, Kirkendall voids and Bi segregation at the IMC/Cu interface were realized with Cu-Zn substrate under isothermal solid aging. Joint strength and fracture behavior were also improved by Cu-Zn substrate. There was no obvious decreasing on the joint strength and the fracture during bending was mainly occurred in the solder matrix with ductile fracture mode or along the solder/IMC interface with partly brittle fracture mode for Cu-Zn joint compared with the dramatically decreasing on joint strength and brittle fracture mode occurred along the interface between IMC and Cu for Sn-Bi/Cu joints after aging. •Minor Zn in Cu pad improves the interfacial structure and mechanical behavior of Sn-Bi joint.•IMC growth was depressed, and Bi segregation and Kirkendall voids were avoided.•Fracture was transformed from brittle mode into ductile or partly brittle mode.